Um estudo historiográfico sobre a psicanálise com crianças no contexto universitário - Silva, Iúri Yrving Müller [UNESP] (2015)
Child Psychoanalysis starts its journey in Europe in the early twentieth century, marked by the pioneering contributions of Melanie Klein and Anna Freud. In Brazil, this type of psychoanalytic service began to be widespread from the 1930s and ended up spreading in well-structured institutional practices, culminating in significant theoretical production. Futhermore, under the auspices of Psychoanalysis Societies, this branch of psychoanalytic science has found greater resonance to its implementation, dissemination, training of child analysts and theoretical work which, though not bulky, has been highly significant. Similarly, academia, through its scientific production, is devoting greater attention to understanding the influences that psychoanalysis has on the way we approach the subject, which has been present in Psychology courses since they were inaugurated in 1960. Since the 1980s, we can observe an auspicious phenomenon, the reception of psychoanalysis by graduate courses in various universities. Therefore, the university encouraged the growth of theoretical literature on the topic, for it didn't aim at a strict analytic training, but at representing a more neutral environment, better able to stimulate and to accept the myriad of points of view than the psychoanalytic institution. Through the analysis of theses and dissertations produced in graduate courses in psychology over the past decade, this research aims at investigating the psychoanalytic theoretical work on children in the twenty-first century, basing on the academic scientific production of that period. Taking the contextual historical method as a reference, the research initially consisted of a bibliographical survey on the topic in national dissertations and theses, from 2000 to 2010. Basing on the results, four categories have been defined, considering the nature of the work: conceptual, psychoanalysis with children...